Looking Beyond the Screen: A Critical Review of the Literature on the Online Child Pornography Offender. (August 2017) - Henshaw, Marie; Ogloff, James R. P.; Clough, Jonathan A.
This article reviews the current literature pertaining to those who engage in child pornography offending. The basic characteristics of online child pornography offenders (CPOs) and related typologies are briefly presented prior to reviewing the comparative literature pertaining to CPOs and child contact sexual offenders. In general, CPOs have been found to be relatively high functioning and generally pro-social individuals with less extensive and diverse offending histories than contact offenders. CPOs also display high levels of sexual pre-occupation, deviant sexual interests, and deficits in interpersonal and affective domains that surpass those of contact offenders. Although further research is required to replicate and clarify preliminary findings, the available evidence indicates that existing sexual offender risk assessment tools and treatment programs are not suitable for use with CPOs, and thus require revision and empirical evaluation prior to widespread use among this population. The article concludes with implications for clinical practice and directions for future research.